Mechanical Performance of Kenaf / Wheat Straw Bio-compsite Panels Bonded with Urea Formaldehyd - Hassan Fwaz, Solafa Elsir; Elarabi, Salaheldin M.; Osman, Zeianb; Eltayeb, Musa (Gezira Journal of Engineering and Applied Sciences; Vol 17 No 1 (2022), 2026)
The pursuit of sustainable construction materials requires exploring bio-composites as alternative to conventional particle board used in green buildings. This study has evaluated the mechanical properties of bio-composite panels made from a mixture of " kenaf fibers: wheat straw fibers" with urea-formaldehyde (UF) resin as a sustainable alternative to conventional particle board.  Two types of panels were analyzed: standard specimen (S) and specimen (A) (kenaf: wheat straw) (50:50). Key properties, which were assessed, included tensile strength, stress, strain, modulus of rupture (MOR), modulus of elasticity (MOE), density, internal bond (IB) and young’s modules.  Specimen (A) exhibited a tensile strength of (22.2) MPA, compared with specimen (S), which had the value of 23.4 MPA. Specimen (A) exhibited a stress of (20.4) MPA, compared with specimen (S), which had the value of 22.3 MPA.  Specimen (A), also, showed a strain of (0.8 %) compared with the specimen (S), which exhibited the value of 1.2%. It also displayed MOR of (20.6) MPA, compared with the specimen (S), which had the value of 21 MPA. Specimen (A) also manifested MOE of (2.2) GPA, compared with the specimen (S), which showed the value of 2.6 GPA. It also recorder a density of (0.58) g/cm 3 compared with the specimen (S), which had the value of 0.6 g/cm 3 . Further, specimen (A) showed IB of (0.63) MPA, compared with the specimen (S), which had the value of 0.9 MPA.  It also exhibited young’s modules of (2550) MPA, compared with specimen (S), which showed the value of 2500 MPA. This study has concluded that specimen (A) showed mechanical properties which were very close to standard specimen (S). The tensile strength, MOR, MOE, young′s modulus and strain obtained were excellent, and the stiffness was very good , but it showed lower flexibility and slight decrease in internal bonding. It can be concluded, according to the findings of this study, that specimen ( A ) could be used for interior panels and furniture in green buildings. The study recommends using additional proportions of kenaf fibers, improving the mechanical properties of specimens by increasing the fiber proportions, and increasing the resin content. Furthermore, applying higher mold pressure and increasing density, both, enhance  the MOR, MOE and IB values and make specimens more suitable for industrial applications and green building construction.